Measurement of human immunodeficiency virus type 1 p24 in serum by an ultrasensitive enzyme immunoassay, the two-site immune complex transfer enzyme immunoassay. - Hashida, S (1995)
Human immunodeficiency virus type 1 (HIV-1) p24 antigen was measured by an ultrasensitive enzyme immunoassay (two-site immune complex transfer enzyme immunoassay). The antigen was reacted simultaneously with 2,4-dinitrophenyl-biotinyl-bovine serum albumin-anti-recombinant p24 (rp24) Fab' conjugate and anti-rp24 Fab'-beta-D-galactosidase conjugate. The complex that was formed, comprising the three components, was transferred from polystyrene beads coated with affinity-purified (anti-2,4-dinitrophenyl group) immunoglobulin G (IgG) to polystyrene beads coated with streptavidin. The detection limit of rp24 was 2.4 fg (0.1 amol) per assay or 0.24 pg/ml with as little as 10 microliters of serum. When sera were treated at low pH, p24 was detected in 34 (68%) of 50 serum samples from asymptomatic carriers, in 25 (86%) of 29 serum samples from patients with advanced HIV-1 infection, and in none of 117 serum samples from HIV-1-seronegative individuals. Levels of p24 in serum were inversely correlated to those of anti-HIV-1 p24 IgG, and the recovery of rp24 added to serum decreased to zero with increasing levels of anti-HIV-1 p24 IgG in serum. This sensitive method may be used as a powerful tool for investigating the disease.